Ważniejsze propozycje zmian kodeksu karnego wykonawczego w odniesieniu do kary pozbawienia wolności - Tobis, Aleksander (Wydział Prawa i Administracji UAM, 1983)
The article discusses changes of legal state pertaining execution of deprivation of liberty which are proposed by the Committee, specially appointed by the Minister of Justice, to be introduced in the Polish punishment execution code. The author submits- his remarks on the proposed changes and suggests his original legal regulation of some executory problems proving it with reasons. The following questions are dealt with in the article: changes of sec. 37 of the punishment execution code (hereinafter called the p.e.c.) and of sec. 80 of the penal code (hereinafter called the p.c.) concerning teleological aspects of execution of deprivation of liberty penalty. The author seeks to eliminate double regulating these questions in the p.e.c. and the p.c. The new content of sec. 37 of the p.e.c. is proposed with the allowance made, apart of general resocializing premises, for the certain marigin of punitive treatment of condemned persons not requiring resocialization. Changes in the structure of penal institutions and in grounds for classification of the sentenced persons are also discussed. Two new institutions are to be created in that scope: for the persons sentenced for unintentional offences and for serving the arrest sentence in a case of a petty offence. According to their types penal institutions are to be divided into closed, semi-open and open ones. The criterion of character of an offence is to be eliminated in the classification while the elements related to the personality of a perpetrator are to be more emphasised; psychological and penitentiary examination of the sentenced persons are to be introduced on a wider scale. Sentenced persons have to enjoy more rights while serving their sentences, especially in executory proceedings, in enjoying and exercising religious practices, in self-education, in including, under some conditions, the periods of employment to old age pensions, in extending periods of a rest leave, in assistance in the social adaptation upon release from a penal institution etc. The problem of means of penitentiary treatment: of work, education, cultural and instructional classes as well as of rewards and disciplinary proceedings are also discussed in the article. The article is closed with conclusions and proposition of egal regulation.
Significant propositions of changes in the Punishment Execution Code with regards to the penalty of deprivation of liberty